Asia Pacific trade facilitation report 2021 supply chains of critical goods amid the COVID-19 pandemic disruptions, recovery, and resilience. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Supply chain disruptions caused by the pandemic have underscored the need for digital and paperless trade procedures. A special chapter examines the pandemic impact on the supply chains of critical goods such as vaccines, personal protective equipment, and food, and provides policy suggestions for enhancing supply chain resilience and trade facilitation. This is the third biennial progress report on trade facilitation implementation in Asia and the Pacific jointly prepared by the Asian Development Bank and the United Nations Economic and Social Commission for Asia and the Pacific.
Keywords: Public health; COVID -19, disease; Economic integration; Electronic book